Resepsi Al-Qur’an Umat Islam Kota Kediri Terhadap Wabah Covid-19 - M. Zaenal Arifin; Zainal Muttaqin (Prodi Studi Agama-agama Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2023)
This article examines the reception of the Qur'an in Kediri City Muslims against the covid-19 outbreak. This type of research is qualitative research, by basing the data collection method on literature study and field study at once. Furthermore, based on the data obtained, the author tries to analyze using phenomenological analysis and content analysis. The results obtained are that there are five typologies of Qur'anic receptions in Kediri City Muslims towards the Covid-19 outbreak, namely: First, those who interpret that this plague is essentially God's punishment, namely a curse from Allah SWT, God is angry and then sends his punishment. The second view says that this plague is essentially a kind of natural disaster. Changes in the ecosystem of the environment then cause this plague. Third, the view that this plague is essentially a form of major correction for human mistakes, mistakes in caring for the ecosystem, mistakes in caring for the environment then an imbalance arises then this plague is born. Fourth, the view that says that this plague is a test, a form of trial that Allah SWT sent down, deliberately revealed to His servants who were chosen to be upgraded. The process of upgrading must go through a test, through trials so that those who pass will rise in degrees. Fifth, the view that this plague is a form of grace, the love of Allah SWT because with this plague many things, many positive sides are felt.